2018
DOI: 10.2147/cmar.s142019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of marital status on survival of hepatocellular carcinoma by race/ethnicity and gender

Abstract: PurposeIt is well demonstrated that being married is associated with a better prognosis in multiple types of cancer. However, whether the protective effect of marital status varied across race/ethnicity and gender in patients with hepatocellular carcinoma remains unclear. Therefore, we aimed to evaluate the roles of race/ethnicity and gender in this relationship.Patients and methodsWe identified eligible patients from Surveillance, Epidemiology and End Results (SEER) database during 2004–2012. Overall and canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Moreover, married patients had superior OS than their unmarried competitors. One explanation for this could be the difference in health-care seeking behavior between married and unmarried patients 33,34…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, married patients had superior OS than their unmarried competitors. One explanation for this could be the difference in health-care seeking behavior between married and unmarried patients 33,34…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is the fifth most frequently occurring cancer and the third leading cause of cancer-related death. 1 , 2 Most patients are found in the advanced stage, and the prognosis of HCC is extremely poor due to the frequent metastasis, relapse, and chemotherapy resistance. 3 5 Therefore, understanding the molecular mechanisms underlying the initiation and development of HCC may lead to the improvement of clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research showed that marital status is one factor affecting prognosis [22,23] ; this may be because a close and cohesive family increases the likelihood of adherence, and psychological and economic support from spouses may contribute to improvements in survival in married patients [24][25][26] . Furthermore, several studies based on the SEER database indicated that HCC patients who were married had a better prognosis [27][28][29] . However, our competitive risk analysis showed that marital status was signi cantly associated with well OS but not CSS.…”
Section: Discussionmentioning
confidence: 99%